Venous access catheter-related thrombosis in patients with cancer. Issue 3 (March 2014) - Gaddh, Manila; Antun, Ana; Yamada, Kei; Gupta, Pooja; Tran, Ha; El Rassi, Fuad; Kim, Hyun S.; Khoury, Hanna Jean
Abstract Patients with cancer are at high risk for developing venous thromboembolism (VTE), and the presence of a central venous catheter (CVC) further increases this risk. CVC-related VTE has serious implications related to the loss of vascular access, development of pulmonary embolism, recurrent VTE, infections and post-thrombotic syndrome. The pathogenesis of CVC-related VTE is complex and multifactorial, with risk factors associated with the catheter, the vessel selected for insertion and the underlying cancer as well as the anti-cancer therapy. Clinical presentation of CVC-related VTEs is often non-specific, and ultrasonography is the most commonly used radiological diagnostic test. Management of CVC-related VTE in patients with cancer requires a balance between the need for venous access, the risk of VTE recurrence and the risk of bleeding from treatment-induced thrombocytopenia. Effective VTE prophylaxis methods have yet to be defined. Ongoing studies are evaluating the role of newer oral antithrombotic agents and alternative interventional strategies for the prevention and treatment of CVC-related VTE in patients with cancer.